Complete Sequence Analysis of Grapevine Leafroll-Associated Virus 4 and Interactions Between the Encoded Proteins - Tingting Du; Yuxin Hao; Jie Gao; Shane Qiao; Guojun Hu; Fang Ren; Xudong Fan; Yafeng Dong (Viruses)
Grapevine leafroll disease is one of the most devastating diseases in the global viticulture industry. Grapevine leafroll-associated virus 4 is one of the main pathogens causing this disease. In this study, we obtained the complete genome sequences of two Chinese isolates of GLRaV-4 from ‘Baisainie’ and ‘Fantasy Seedless’ grapevines through high-throughput sequencing and overlapping RT-PCR combined with RACE technology. The sequences contain 13,814 and 13,824 nucleotides and code six open reading frames, respectively. Phylogenetic trees based on the coat protein (CP) and heat shock protein 70 (HSP70) genes show that in addition to other GLRaV-4 strains (strains 5, 6, 9, Pr, and Car), the GLRaV-4 strains were divided into two distinct groups. The two isolates obtained in this study were classified into separate branches within GLRaV-4 Group 1. Additionally, we systematically investigated the interactions between the proteins encoded by GLRaV-4 using the yeast two-hybrid and bimolecular fluorescence complementation techniques. We found significant interactions between the GLRaV-4-encoded p23 and HSP70 and CP. This study first reports the complete genomes of two different GLRaV-4 isolates from China and suggests that p23 protein encoded by GLRaV-4 may play an important role in viral pathogenicity due to its interactions with the other two proteins.